Guiding principles for utilizing social influence within expert‐elicitation to inform conservation decision‐making. (30th March 2020) - Roy, Helen E.; Peyton, Jodey M.; Booy, Olaf
Abstract : Many hundreds of people have engaged with our collaborative studies using expert‐elicitation approaches through facilitated discussions to dynamically inform decision‐making within the field of biological invasions. We draw on our experiences to outline ways that allow the inclusion of multiple viewpoints within expert‐elicitation while limiting or transparently documenting potential bias.